BIOMASS PRODUCTIVITY IN MAJOR ECOSYSTEMS OF COLD DESERTS OF HIMACHAL PRADESH - POONAM; R. BAWA (The Bioscan, 2019)
The present study was conducted at village Goshal, one of the largest villages of cold desert district (Lahaul spitti), in Himachal Pradesh, India, during 2010 to 2013. Biomass productivity was studied by classifying the study area into two major ecosystems viz; Alpine pasture ecosystem and agro ecosystem. Aboveground and belowground biomass studies showed that in alpine ecosystem Agropyron longearistatum had maximum total aboveground biomass 0.99 kg/m2 among grasses and Taraxacum officinale had maximum total biomass 0.86 kg/m2 among herbaceous species. While Sassuria lappa had maximum total biomass of 1.62 kg/m2 among herbs in agro ecosystem and potato showed the maximum total biomass 7.29 kg/m2 among crops in agro ecosystem. Thus it was observed that the species had higher biomass in agro ecosystem as compared to alpine pasture ecosystem.